Targeted locus amplification to detect molecular markers in mantle cell and follicular lymphoma. Issue 3 (31st March 2021) - Genuardi, Elisa; Klous, Petra; Mantoan, Barbara; Drandi, Daniela; Ferrante, Martina; Cavallo, Federica; Alessandria, Beatrice; Dogliotti, Irene; Grimaldi, Daniele; Ragaini, Simone; Clerico, Michele; Lo Schirico, Mariella; et al.
Abstract: Minimal residual disease (MRD) monitoring by PCR methods is a strong and standardized predictor of clinical outcome in mantle cell lymphoma (MCL) and follicular lymphoma (FL). However, about 20% of MCL and 40% of FL patients lack a reliable molecular marker, being thus not eligible for MRD studies. Recently, targeted locus amplification (TLA), a next‐generation sequencing (NGS) method based on the physical proximity of DNA sequences for target selection, identified novel gene rearrangements in leukemia. The aim of this study was to test TLA in MCL and FL diagnostic samples lacking a classical, PCR‐detectable, t (11; 14) MTC (BCL1/IGH), or t (14; 18) major breakpoint region and minor cluster region (BCL2/IGH) rearrangements. Overall, TLA was performed on 20 MCL bone marrow (BM) or peripheral blood (PB) primary samples and on 20 FL BM, identifying a novel BCL1 or BCL2/IGH breakpoint in 16 MCL and 8 FL patients (80% and 40%, respectively). These new breakpoints (named BCL1‐TLA and BCL2‐TLA) were validated by ASO primers design and compared as MRD markers to classical IGH rearrangements in eight MCL: overall, MRD results by BCL1‐TLA were superimposable (R Pearson = 0.76) to the standardized IGH‐based approach. Moreover, MRD by BCL2‐TLA reached good sensitivity levels also in FL and was predictive of a primary refractory case. In conclusion, this study offers the proof of principle that TLA is a promising and reliable NGS‐based technology for the identification of novel molecular markers, suitable for further MRD analysis in previously not traceable MCL and FL patients.